2018
DOI: 10.1002/mnfr.201800512
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index as a Determinant of Systemic Exposure to Gallotannin Metabolites during 6‐Week Consumption of Mango (Mangifera indica L.) and Modulation of Intestinal Microbiota in Lean and Obese Individuals

Abstract: Scope This human clinical pilot trial investigated pharmacokinetics of gallotannin‐metabolites and modulation of intestinal microbiota in healthy lean and obese individuals after 6 weeks of daily mango consumption. Methods and results Participants are divided into three groups: Lean Mango (LM: n = 12; BMI = 22.9 kg m−2), Obese Mango (OM: n = 9; BMI = 34.6 kg m−2), and Lean Control (LC: n = 11; BMI = 22.1 kg m−2). LM and OM consumed 400 g of mango per day for 6 weeks. LC consumed mango only on Days 0 and 42. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 70 publications
(108 reference statements)
2
25
0
Order By: Relevance
“…These results are in agreement with previous studies on mango conducted by the Talcott group where they observed significant (p < 0.05) increases of pyrogallol and benzoic acid derivatives in urine including methylpyrogallol sulfate, pyrogallol sulfate and methylgallic acid sulfate after consumption of MP [20,52,53]. The increased excretion of mango (poly)phenol (mainly gallotannins) metabolites could be due to the adaptive increase in microbial metabolism after 14 days of daily intake of mango polyphenols [4,33,54].…”
Section: Short-term 14 Day Mango Feeding Trialsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with previous studies on mango conducted by the Talcott group where they observed significant (p < 0.05) increases of pyrogallol and benzoic acid derivatives in urine including methylpyrogallol sulfate, pyrogallol sulfate and methylgallic acid sulfate after consumption of MP [20,52,53]. The increased excretion of mango (poly)phenol (mainly gallotannins) metabolites could be due to the adaptive increase in microbial metabolism after 14 days of daily intake of mango polyphenols [4,33,54].…”
Section: Short-term 14 Day Mango Feeding Trialsupporting
confidence: 91%
“…For example, colon microorganisms such as Lactobacillus plantarum, Streptococcus galloylitcus, Aspergillus oryzae and Lactococcus lactis can utilize gallotannins and produce gallic acid, pyrogallol and catechol [47,55]. Previous studies in humans demonstrated that repetitive mango supplementation can increase the abundance of pyrogallol-producing microbiota, e.g., Aspergillus oryzae and Lactococcus lactis, and decrease the abundance of Bacteroides thetaiotaomicron and Clostridium leptum [47,53]. Additionally, gallotannins and their metabolites may inhibit growth of other bacteria such as Bacteroides fragilis, Escherichia coli, Enterobacter cloacae, Salmonella typhimurium, Salmonella aureus, etc.…”
Section: Short-term 14 Day Mango Feeding Trialmentioning
confidence: 99%
“…Recently, we have reported that daily consumption of GT‐rich mango pulp for 6 weeks increases levels of tannase‐producing bacteria ( Lactococcus lactis ) in healthy human subjects, and this increase was correlated with increased tannase enzyme activity in fecal samples. The production of a short‐chain fatty acid, namely butyrate, showed a trend toward increased levels after 6 weeks of mango consumption . This evidence suggests that the health‐promoting effects of GT and L. plantarum may be at least in part based on prebiotic–probiotic interactions between GT and L. plantarum .…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, in another human clinical study, Barnes et al identified five gallotannin metabolites (4- O -methylgalic acid, 4- O -methylgalic acid-3- O -sulfate, pyrogallol- O -sulfate, methylpyrogallol- O -sulfate, and catechol- O -sulfate) in plasma and urine. These results demonstrated the absorption of these metabolites in the colon into plasma and urinary excretion within 24 h of ingestion [ 39 ].…”
Section: Bioavailability and Intestinal Metabolism Of Mango Polyphenolsmentioning
confidence: 97%